Is it all in the eye of the beholder? The importance of situation construal for situational judgment test performance - Jan-Philipp Freudenstein; Philipp Schäpers; Lena Roemer; Patrick Mussel; Stefan Krumm (Personnel Psychology, 2020)
Recent research challenges the importance of situation descriptions for situational judgment test (SJT) performance. This study contributes to resolving the ongoing debate on whether SJTs are situational measures, by incorporating findings on person situation interactions into SJT research. Specifically, across three studies (NTotal~=~1,239), we first tested whether situation construal (i.e., the individual perception of situations in SJTs) predicts responses to SJT items. Second, we assessed whether the relevance of situation construal for SJT performance depends on test elements (i.e., situation descriptions and response options) and item features (i.e., description-dependent vs. description-independent SJT items). Lastly, we determined whether situation construal has incremental validity for job-related criteria over and above SJT performance. The results showed that, for most SJT items, situation construal significantly contributed to SJT performance, even if only response options were available. This was also true for SJT items that are significantly more difficult to solve when situation descriptions are omitted (i.e., description-dependent SJT items). Finally, situation construal explained variance in relevant criteria over and above SJT performance. Despite recent efforts to reconceptualize SJTs, our results suggest that they can still be viewed as situational measures. However, situation descriptions may be less crucial for these underlying situational processes. Theoretical and practical implications are discussed.
Keywords: 650; person situation interaction; situation construal; situational judgment test; validity